Genetic Variations Controlling Regulatory T Cell Development and Activity in Mouse Models of Lupus-Like Autoimmunity - Roach, Tracoyia; Morel, Laurence (Frontiers in Immunology, 2022)
Immune homeostasis is a constant balancing act between effector T cells and regulatory T cells defined by Foxp3 expression, the transcription factor that drives their differentiation and immunosuppressive activity. Immune homeostasis is altered when Treg cells are not generated or maintained in sufficient numbers. Treg cells rendered unstable by loss of Foxp3 expression, known as ex-Treg cells, gain pro-inflammatory functions. Treg cells may also become dysfunctional and lose their suppressive capabilities. These alterations can cause an imbalance between effector and regulatory subsets, which may ultimately lead to autoimmunity. This review discusses recent studies that identified genetic factors that maintain Treg cell stability as well as preserve their suppressive function. We focus on studies associated with systemic lupus erythematosus and highlight their findings in the context of potential therapeutic gene targeting in Treg cells to reverse the phenotypic changes and functional dysregulation inducing autoimmunity.